2023
DOI: 10.1093/europace/euad004
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial appendage closure device outcomes among cirrhosis patients with atrial fibrillation: a United States National Cohort Study

Abstract: Aims Literature regarding outcomes associated with atrial fibrillation among cirrhosis patients who had left atrial appendage occlusion (LAAO) device procedure is limited. We aim to evaluate the in-hospital clinical outcomes and 30-day readmissions among LAAO with and without cirrhosis. Methods and results We performed a retrospective study of all hospitalizations associated with the LAAO procedure, using the Nationwide Readm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“… 27–30 In a study evaluating the prognostic value of CKD in patients undergoing LAAO, moderate-to-severe CKD was associated with a higher incidence of the primary composite endpoint of cardiovascular mortality, thromboembolism, and major bleeding. 27 Similarly, among patients undergoing LAAO, the presence of heart failure was associated with prolonged LOS and higher hospitalization costs, 28 the presence of cirrhosis was associated with higher rates of 30-day readmission, 29 and the presence of a higher CHA 2 DS 2 -VASc score was associated with an increased risk of peri-procedural complications and resource utilization. 30 Female sex has also been associated with worse in-hospital outcomes following LAAO compared with men.…”
Section: Discussionmentioning
confidence: 99%
“… 27–30 In a study evaluating the prognostic value of CKD in patients undergoing LAAO, moderate-to-severe CKD was associated with a higher incidence of the primary composite endpoint of cardiovascular mortality, thromboembolism, and major bleeding. 27 Similarly, among patients undergoing LAAO, the presence of heart failure was associated with prolonged LOS and higher hospitalization costs, 28 the presence of cirrhosis was associated with higher rates of 30-day readmission, 29 and the presence of a higher CHA 2 DS 2 -VASc score was associated with an increased risk of peri-procedural complications and resource utilization. 30 Female sex has also been associated with worse in-hospital outcomes following LAAO compared with men.…”
Section: Discussionmentioning
confidence: 99%
“… 16 , 17 It has emerged as a non-pharmacologic alternative to OAC, particularly in patients at high risk for major bleeding. 1 , 18 The PRAGUE-17 trial compared LAAO with DOAC in 402 patients with AF at high risk of stroke and bleeding and showed no inferiority in terms of the net clinical endpoint of thromboembolic complications and bleeding in follow-up for up to 4 years. 19 , 20 …”
Section: Discussionmentioning
confidence: 99%
“…In this edition of Europace , Mir and colleagues present a retrospective analysis of LAAO procedural outcomes in patients with cirrhosis compared to those without. 2 Using the National Readmissions Database, which covers almost half of all hospitalizations in the USA, the authors identified over 54 000 LAAO procedures performed between 2016 and 2019, of which 905 (1.65%) had cirrhosis. Patients with cirrhosis were younger, but had higher rates of comorbidities including heart failure, diabetes, obesity, chronic renal failure, cancer, and alcohol use as compared to those without.…”
Section: Introductionmentioning
confidence: 99%